2017
DOI: 10.1079/pavsnnr201712014
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap to a One Health agenda 2030.

Abstract: The current fragmented framework of health governance for humans, animals and environment, together with the conventional linear approach to solving current health problems, is failing to meet today's health challenges and is proving unsustainable. Advances in healthcare depend increasingly on intensive interventions, technological developments and expensive pharmaceuticals. The disconnect grows between human health, animal health and environmental and ecosystems health. Human development gains have come with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 91 publications
(109 reference statements)
1
42
0
Order By: Relevance
“…The “One Health” initiative recommends multidiscipline collaboration for an increase in sustainable and cost‐effective approaches in preventing infectious diseases as well as other public health interventions (Queenan et al, ). Likewise, the new Sustainable Development Goals published by WHO in 2015 (World Health Organization, ), stresses the necessity of an integrated approach across environmental, economic and social pillars to address all infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The “One Health” initiative recommends multidiscipline collaboration for an increase in sustainable and cost‐effective approaches in preventing infectious diseases as well as other public health interventions (Queenan et al, ). Likewise, the new Sustainable Development Goals published by WHO in 2015 (World Health Organization, ), stresses the necessity of an integrated approach across environmental, economic and social pillars to address all infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, therefore, as a decisive element in policy development, knowledge integration could help resolve the main shortcomings of the current global framework for health governance, by managing complexity and shaping interactions between actors and institutions towards joint learning 17 , 18 . Knowledge integration could also be used to complement educational and institutional measures for improving the implementation of the One Health approach 14 . We therefore propose that policy cycles relevant to One Health should aim at knowledge integration and make the best possible use of multicriteria analyses, systems thinking and transdisciplinary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some of the current framework’s shortcomings could be overcome by the development of coordinated supranational bodies, the promotion of specialized training and career opportunities and the creation of dedicated funding mechanisms 9 , 12 14 . We suggest that the framework may also be strengthened by improving the integration of its management 4 , 7 , 15 and by integrating knowledge at all stages of any related policy development 16 18 .…”
Section: Introductionmentioning
confidence: 96%
“…Despite the ‘good’ intentions the SDGs, there have been questions about their level of complexity, including the political and governance capacities for them to be realised (Liverman, 2018). The ‘SDGs provide a key entry point for the OH approach to drive a paradigm shift in policy and practice towards a fully integrated approach’ (Queenan et al, 2017, p. 6). However, Waage et al (2015) cited in Queenan et al (2017, p. 5) ‘criticises the SDGs for being developed within different sectors and presented by the UN without recognizing the interactions’.…”
Section: The Sdgs and Ihrs: Multi‐level Leadershipmentioning
confidence: 99%
“…The ‘SDGs provide a key entry point for the OH approach to drive a paradigm shift in policy and practice towards a fully integrated approach’ (Queenan et al, 2017, p. 6). However, Waage et al (2015) cited in Queenan et al (2017, p. 5) ‘criticises the SDGs for being developed within different sectors and presented by the UN without recognizing the interactions’. Urbanization, and risks of urban animals producing health threats, risk being lost within the web of SDGs given that health and the environment‐related SDGs cover a broad range of areas.…”
Section: The Sdgs and Ihrs: Multi‐level Leadershipmentioning
confidence: 99%